Impact of radiation in a stagnation point flow of Walters' B fluid towards a Riga plate. (June 2018) - Shafiq, Anum; Hammouch, Z.; Turab, Ali
Graphical abstract: Highlights: The stagnation point flow of Walters-B fluid induced by a Riga plate is s investigated. Heat transfer properties are investigated with thermal radiation effect and Newtonian heating. An electromagnetic actuator is a Riga-plate where a span wise associated array of irregular electrodes and permanent magnets mounted on a surface. Graphical results for the dimensionless velocity and temperature are presented and discussed for various physical parameters and Local skin friction. Local Nusselt numbers are computed analytically using OHAM. Abstract: In this article, the stagnation point flow of Walters-B fluid induced by a Riga plate is investigated. Heat transfer properties are investigated with thermal radiation effect and Newtonian heating. An electromagnetic actuator is a Riga-plate where a span wise associated array of irregular electrodes and permanent magnets mounted on a flat surface. Lorentz force is parallel to a surface which is generated by this array and it reduces exponentially in the direction normal to the surface. The non-linear ordinary differential equations through the fundamental laws of mass, linear momentum and energy are obtained using the suitable transformation. The optimal values of convergence control parameters are computed by means of Optimal homotopy analysis method (OHAM) via BVPh2.0. Graphical results for the dimensionless velocity and temperature are presented and discussed for various physical parameters. Local skin friction and Local Nusselt numbers are computed analytically using OHAM.